A Study On Consumer Perception Towards Promotional Messages With Special Reference To Coimbatore City - S Renugadevi; P Ramakrishnan (Journal of Advanced Research in HR and Organizational Management, 2021)
Promotional messages are the type of personal selling where the customers are contacted individually. Promotional message is the communication about the product/service that a company wants to deliver to its target customers in order to generate awareness and subsequent sales. Promotional messages maybe in various forms, the most common forms being text messaging and email. Hence this study is focused on consumer perception towards Promotional messages in Coimbatore City. It was found that customers are overloaded with promotional messages. It acts as a good marketing strategy. It is also found that the buying behavior is significantly influenced by promotional messages. Mostly customers are receiving promotional messages through SMS only. Daily messages are sometimes irritating for customers that can be avoided. Majority of the customers are felt that promotional messages are useful. How to cite this article: Renugadevi S, Ramakrishnan P. A Study on Consumer Perception Towards Promotional Messages with Special Reference To Coimbatore City. J Adv Res HR Organ Mqmt 2021; 8(1&2): 1-4.